Picturing Participation: Catalyzing Conversations About Community Engagement in HIV Community–Based Organizations. (December 2021) - Switzer, Sarah; Chan Carusone, Soo; McClelland, Alex; Apong, Kamilah; Herelle, Neil; Guta, Adrian; Strike, Carol; Flicker, Sarah
Community engagement is considered a cornerstone of health promotion practice. Yet engagement is a fuzzy term signifying a range of practices. Health scholarship has focused primarily on individual effects of engagement. To understand the complexities of engagement, organizations must also consider relational, structural, and/or organizational factors that inform stakeholders' subjective understandings and experiences. Community engagement processes are not neutral; they can reproduce and/or dismantle power structures, often in contradictory or unexpected ways. This article discusses diverse stakeholders' subjective experiences and understandings of engagement within the HIV sector in Toronto, Canada. In our study, a team of community members, service providers, and academics partnered with three HIV community–based organizations to do this work. We used photovoice, a participatory and action-oriented photography method, to identify, document, and analyze participants' understandings at respective sites. Through collaborative analysis, we identified seven themes that may catalyze conversations about engagement within organizations: reflecting on journey; honoring relationships; accessibility and support mechanisms; advocacy, peer leadership, and social justice; diversity and difference; navigating grief and loss; and nonparticipation. Having frank and transparent discussions that are grounded in stakeholders' subjective experiences, and the sociopolitical and structural conditions of involvement, can help organizations take a more intersectional and nuanced approach to community engagement. Together, our findings can be used as a framework to support organizations in thinking more deeply and complexly about how to meaningfully, ethically, and sustainably engage communities (both individually and collectively) in HIV programming, and organizational policy change. The article concludes with questions for practice.